The most common parenting styles in Kosovo: perceptions of secondary school students - Ardita Devolli; Veli Kryeziu; Dafina Bujupi (Universidade Estadual de Maringá, 2023)
This study was conducted to analyze Kosovo's most common parenting styles based on secondary school students' perceptions. There are four styles of parenting: 1) Authoritative parents, 2) authoritarian parents, 3) Permissive, tolerant parents, 4) uninvolved (negligent) parents. The study was concluded with secondary school students in two gymnasiums in Klina and Gjakova. Out of 1334 participants who took part in the study, 848 were female, and 486 were male. A quantitative method was used for the analysis. The instrument used for the research is the Parenting Style Scale (Gafor & Kurukkan, 2014). Each statement was conducted with a paired sample t-test and independent sample t-test to see the differences between fathers and mothers. Out of 38 statements, secondary school students showed statistically significant values that mothers are authoritative in 14 statements and permissive in 12 of them. At the same time, fathers are not authoritative but are tolerant in only one statement. According to female perceptions, mothers are more authoritative and permissive than fathers, while based on male perceptions according to the authoritative style, mothers and fathers are equally authoritative. According to the permissive style, fathers are more tolerant than mothers. In Kosovo, mothers are much more involved in parenting compared to fathers.